EFL SPEAKING STUDENT READINESS TO USE MOBILE-ASSISTED LANGUAGE LEARNING - Assapari, Muhammad Mugni; Hidayati, Rosyadi (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
In recent years, mobile-assisted language learning has been on the rise as an instructional approach. While some innovative media platforms have been highly studied, Thus, this study focused on how students' readiness and learning outcomes the use of mobile phones to facilitate individualized instruction in public speaking as part of an English as a Foreign Language course. Data were collected from (n=42) students in non-English department classes who participated in this study. They were asked to answer an online questionnaire that surveyed their readiness and outcomes using Google Foam in their speaking skills. All participants performed two class projects aimed at aiding them in exploring mobile-assisted language learning using their own mobile devices. However, the students self-reported some opportunities and benefits for English Foreign Language Learners (EFLL) among these MALL users. The results of this study suggest that EFL-speaking students' readiness affects mobile-assisted language learning. Teachers should consider students' motivation, attitudes, and technology skills when creating mobile-assisted language learning programs. Instructors should also train and motivate pupils to use mobile-assisted language learning resources by improving their technology skills. Furthermore, need for further technical support and facilitating students' mastery of speaking performance.